Pengembangan Bahan Ajar E-Magazine dengan Pendekatan SAVI pada Materi Dinamika Litosfer dan Dampaknya Terhadap Kehidupan - Nurhasanah Nurhasanah; Budi Handoyo; Listyo Yudha Irawan (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
The development of 21st century education affects the use of learning media. In learning activities, digital teaching materials are needed that support the student's learning process. The development of e-magazine teaching materials for lithosphere dynamics materials is carried out because digital teaching materials are minimally used in learning. The purpose of this research is to produce e-magazine teaching materials with the SAVI approach. This study used the ADDIE (Analyze, Design, Development, Implementation, and Evaluation) model procedure. The types of data used are quantitative and qualitative. In the process of collecting data using questionnaires, interviews, as well as documentation of activities with percentage descriptive data analysis techniques. Teaching material products are tested for feasibility at SMA Negeri 2 Malang class XI IPS 3. Based on the results of product feasibility tests by media expert validators, material experts, linguists and test results in schools, e-magazine teaching materials are very feasible and valid for geography learning.